A rare triad of Rosai-Dorfman disease: A case report - Tripathi, Mridul; Srivastava, Anand; Garg, Rajiv; Singh, Pradyumn (Indian Journal of Case Reports, 2025)
Rosai-Dorfman disease (RDD) is a rare, benign non-Langerhans cell histiocytosis characterized by the accumulation of CD68⁺, S100⁺, and CD1a⁻ histiocytes, typically presenting as massive, painless cervical lymphadenopathy. Pulmonary involvement in RDD is exceedingly rare. It may manifest with respiratory symptoms, such as chronic cough, dyspnea, and chest pain. We describe the case of a 23-year-old male with immune-related RDD and coexistent juvenile idiopathic arthritis (JIA), who presented with fever, chronic cough, and progressive dyspnea. Imaging revealed extensive bilateral pulmonary involvement and lymph node histopathology confirmed RDD. During hospitalization, the patient developed a right-sided secondary spontaneous pneumothorax, a complication not previously reported in pulmonary RDD. This case highlights the unusual co-occurrence of RDD and JIA with extensive pulmonary involvement culminating in spontaneous pneumothorax. It underscores the importance of considering RDD in the differential diagnosis of atypical pulmonary presentations in young patients, particularly those with underlying autoimmune rheumatic diseases.